Bioactive compounds from Aspergillus niger extract enhance the antioxidant activity and prevent the genotoxicity in aflatoxin B1-treated rats - Abdel-Wahhab, Mosaad Attia; El-Nekeety, Aziza Abdel Salam; Hathout, Amal S.; Salman, Asmaa S.; Abdel-Aziem, Sekena H.; Sabry, Bassem A.; Hassan, Nabila Salah; Abdel-Aziz, Mohammed S.; Aly, Soher E.; Jaswir, Irwandi (Elsevier Ltd, 2020)
This study aimed to identify the bioactive compounds of the ethyl acetate extract of Aspergillus niger SH2-EGY using GC-MS and to evaluate their protective role against aflatoxin B1 (AFB1)-induced oxidative stress, genotoxicity and cytotoxicity in rats. Six groups of male Sprague-Dawley rats were treated orally for 4 weeks included the control group, AFB1-treated group (80 μg/kg b.w); fungal extract (FE)-treated groups at low (140) or high dose (280) mg/kg b.w and the groups treated with AFB1 plus FE at the two tested doses. The GC-MS analysis identified 26 compounds. The major compounds found were 1,2,3,4,6-Penta-trimethylsilyl Glucopyranose, Fmoc-L-3-(2-Naphthyl)-alanine, D-(-)-Fructopyranose, pentakis (trimethylsilyl) ether, bis (2-ethylhexyl) phthalate, trimethylsilyl ether-glucitol, and octadecanamide, N-(2- methylpropyl)-N-nitroso. The in vivo results showed that AFB1 significantly increased serum ALT, AST, creatinine, uric acid, urea, cholesterol, triglycerides, LDL, carcinoembryonic antigen, alpha-fetoprotein, interleukin-6, Malondialdehyde, nitric oxide, Bax, caspase-3 and P53 mRNA expression, chromosomal aberrations and DNA fragmentation. It decreased serum TP, albumin, HDL, Bcl-2 mRNA expression, hepatic and renal TAC, SOD and GPx content and induced histological changes in the liver and kidney. FE prevented these disturbances in a dosage-dependent manner. It could be concluded that A. niger SH2-EGY extract is safe a promising agent for pharmaceutical and food industries.